Interlanguage: a perspective of quantitative linguistic typology. (July 2019) - Jiang, Jingyang; Ouyang, Jinghui; Liu, Haitao
Abstract: The study of interlanguage (IL) is crucial for the understanding of the acquisition and development of human languages. But there are very few empirical investigations into IL from a perspective of general linguistics or/and linguistic typology. Based on a dependency treebank of Chinese EFL learners' English writings from eight consecutive grades, we quantitatively analyzed the typological features of IL. It was found that: (1) Chinese EFL learners' IL linguistic system is a language with SV and VO preference. (2) From the perspective of linguistic typology, IL progressively approaches from native language to target language with the increase of second language proficiency. (3) Dependency direction can well measure learners' IL at different learning stages. (4) The dependency directions of adverbials and attributives can well reflect the typological changes of Chinese EFL learners' IL and learners' language proficiency. Highlights: Chinese EFL learners' IL is a language with SV and VO preference. IL progressively approaches from NL to TL with the increase of proficiency. Dependency direction can measure learners' IL at different learning stages. The DD of adverbials and attributives can reflect the typological changes of IL.